Corrosion Behavior of Titanium Dioxide Nanotubes in Alkaline Solution - Uzal, Hasan; Döner, Ali (MAIK NAUKA/INTERPERIODICA/SPRINGER, 2020)
In this study, titanium dioxide nanotubes (TiO2-NTs) are prepared by using anodization method on commercial pure titanium (Ti) by applying constant voltage of 60 V to the electrolysis system for 15 min, one and two hours. Highly ordered and quality TiO2-NTs layers are formed on Ti electrode. To investigate the corrosion behavior of TiO2-NTs in 1 M KOH solution, electrochemical and surface analysis methods such as anodic and cathodic current-potential curves, electrochemical impedance spectroscopy (EIS), chronoamperometry (CA), scanning electron microscopy (SEM), atomic force microscopy (AFM) and energy dispersive X-ray spectroscopy (EDX) are used. Effect of long immersion time is also studied. Obtained results showed that the corrosion behavior of TiO2-NTs is more improved when compared to bare Ti electrode. Very stable, durable and excellent protective TiO2-NT layer is obtained at anodization time of 1 h. This oxide layer resisted the aggressive solution attack. It is suggested that this oxide layer is used in many industrial applications to reduce the corrosion of commercial pure Ti.
Keywords: TiO2; Corrosion; Alkaline solution